Herbicidal Activity of Aspergillus niger Metabolites Against Parthenium Weed - BASHIR,U. (2018)
ABSTRACT: Metabolites of Aspergillus niger, prepared in malt extract (ME) broth and potato dextrose (PD) broth, were evaluated for their herbicidal activity against a noxious parthenium weed (Parthenium hysterophorus). In laboratory assays, original (X) and diluted (½ X) fungal metabolites significantly reduced germination and seedling growth of weed. However, metabolites prepared in ME broth proved to have greater herbicidal activity than metabolites prepared in other growth medium. Original metabolites prepared in ME broth have completely hinder the germination of parthenium seeds; while those prepared in PD broth have reduced germination by 89% over control. In pot trials, one-week, two-week and three-week-old parthenium seedlings were sprayed three times with original and concentrated (2X) metabolites of A. niger prepared in ME broth. Plants were harvested after 40 days of sowing. One-week treatment plants were most susceptible to fungal metabolites spray, followed by two-week and three-week treatment plants, respectively. Original and concentrated metabolites have significantly reduced shoot biomass of one-week-old plants by 57% and 68%, and root biomass by 50% and 75%, respectively. The present study has come to the conclusion that A. niger metabolites prepared in ME broth can effectively control germination and growth of parthenium.